Fluid Characteristics of Radial Hydrodynamic Bearings Using Supercritical Carbon Dioxide as Lubricant - Chengtao Niu; Sung-Ki Lyu; Yu-Ting Wu; Zhen Qin; Jie Zhang (Lubricants)
Hydrodynamic journal bearings play a vital role in high-speed, heavy-load machinery. Their performance directly affects system efficiency and reliability. Supercritical carbon dioxide (S-CO2), with its favorable thermophysical properties, is a promising lubricant. This study focused on a four-oil-cavity hydrodynamic journal bearing using S-CO2 as the working fluid. A numerical model was established in ANSYS Workbench 2024 R1 using a fluid–structure interaction (FSI) method. The model was validated through comparison with literature data. Parametric studies were conducted by varying radial clearance, eccentricity, inlet diameter, and oil cavity size. Results showed that reducing the oil cavity wrap angle enhanced load capacity. Larger inlet diameters improved lubrication but could increase deformation. An appropriate combination of inlet diameter and eccentricity effectively reduced shell deformation. These findings offer design guidance for S-CO2-lubricated bearings in high-speed applications.